Practical insights into liquid loading within hydraulic fractures and potential unconventional gas reservoir optimization strategies. (September 2015) - Agrawal, Samarth; Sharma, Mukul M.
Highlights: Novel 3D simulation of liquid loading within primary hydraulic fractures and its detrimental effect on gas well productivity. Showed impact of interplay between capillary pressures, gravity and drawdown. Low drawdown or matrix permeability damage leads to inflow velocity reduction and poorer fracture cleanup. Showed that condensate loading in fractures is also possible below dew point. Recommended strategies to minimize liquid back pressure for different scenarios. Abstract: The U.S. has experienced a resurgence of the upstream hydrocarbon sector in recent years, owing to the economic extraction of oil and gas from ultra-tight reservoirs using multistage hydraulic fracturing in horizontal wells. This success is often attributed to slick-water stimulation treatments that help create extensive complexity and contact with the low permeability reservoir. In this process, hundreds of thousands of barrels of water are pumped downhole, along with friction reducers, low concentration linear gel, fracture propping sand and other additives, to create and sustain these fractures. However, only a small percentage of this stimulation water is recovered back once the well is put back on production. This not only leads to excessive water hauling costs for operators in each consecutive well but also liquid blockage for hydrocarbon flow. Such water blockage/loading may become a serious concern in dry gas reservoirs such as the Marcellus field in the northeastern U.S., due to the unfavorable hydrocarbon mobility ratios. In spite of its implications on early and late time well performance, the issue of hydraulic fracture cleanup and gas flowback through it when drained through a horizontal wellbore is still an insufficiently understood subject. In this study the authors investigate the potential of liquid loading (stimulation water or condensate) within the hydraulic fracture itself due to low matrix permeability and insufficient drawdown conditions. Similar conditions may also arise late in the life of well when the reservoir pressure has declined significantly or due to wellbore design issues. A 3D reservoir simulation model with a discrete, planar hydraulic fracture is set up to investigate the competition between capillary, viscous and gravity forces within the fracture. The results indicate a strong tendency for liquid loading in the ultra-low permeability gas reservoirs under common operational constraints and offer recommendations on best practices to minimize its impact.